Problems With Self-Regulation, Family Conflict, and Glycemic Control in Adolescents Experiencing Challenges With Managing Type 1 Diabetes - Vaid, Esha (J Pediatr Psychol, 2018)
OBJECTIVE: This study explored the associations between problems with self-regulation and glycemic control (HbA1c) in teens experiencing challenges with managing type 1 diabetes by examining greater diabetes-related family conflict and poorer adherence as serial mediators of the link between greater problems with self-regulation and higher HbA1c. METHODS: Teens experiencing challenges with managing type 1 diabetes (n = 93, HbA1c ≥8%, 96% White, 57% male) completed an HbA1c test, and their parents completed assessments including measures of adherence and family conflict related to diabetes management during an intake for a larger Web-based intervention study or fMRI study. Teen problems with self-regulation were indexed the Child Behavior Checklist using the dysregulation profile. RESULTS: Bivariate correlations found significant associations between greater problems with self-regulation, greater family conflict about diabetes management, poorer adherence, and higher HbA1c. However, only greater family conflict, and not adherence, significantly explained the association between greater self-regulation problems and higher HbA1c. CONCLUSIONS: These findings suggest that among teens experiencing challenges with managing type 1 diabetes, interventions that decrease family conflict may be critical to promoting optimal glycemic control in those teens with greater problems with self-regulation.